Expression pattern of Ngn3 in dairy goat testis and its function in promoting meiosis by upregulating Stra8. (29th November 2013) - Tang, F.; Yao, X.; Zhu, H.; Mu, H.; Niu, Z.; Yu, M.; Yang, C.; Peng, S.; Li, G.; Hua, J.
Abstract Objectives Ngn3 is a typical transcription factor and marker of differentiating spermatogonial stem cells (SSCs) in mouse, belonging to the basic helix‐loop‐helix (bHLH) family. Its gene is specifically expressed in A type spermatogonia in mouse testis, thus plays a critical role in controlling differentiation of SSCs. However, roles of Ngn3 and its protein in dairy goat testis remain unknown. Materials and methods Testis development and expression patterns of Ngn3 were analysed by immunofluorescence and quantitative reverse transcription‐polymerase chain reaction (QRT‐PCR) in the dairy goat. Furthermore, effects of its overexpression on male germline stem cells (mGSCs) were evaluated by QRT‐PCR, immunofluorescence, luciferase reporter assay and western blotting. Results Revealed that Ngn3 was expressed more highly during puberty and in the adult than in testis of other ages. Overexpression of Ngn3 promoted expression of meiosis‐related gene Stra8 and stem‐cell differentiation marker CD117, but suppressed expression of Plzf, a classical marker of SSCs. Furthermore, Ngn3 did not promote expression of Stra8 directly as shown in transcription and translation levels detected by luciferase reporter assay and western blotting. Conclusions Taken together, these results suggest that Ngn3 plays an important role in spermatogenesis and that overexpression of Ngn3 can promote meiosis in testis of the dairy goat.